The Indonesian Government's Liability Against Forest Fires That Caused Losses to Malaysia : Tanggung Gugat Pemerintah Indonesia Terhadap Kebakaran Hutan yang Mengakibatkan Kerugian Bagi Malaysia - Habibulloh, Rizal Bagus; Phahlevy, Rifqi Ridlo (Rechtsidee, 2021)
This study aims to describe the form of Indonesia's accountability to countries that are directly affected by the haze caused by Indonesian forest fires according to the ASEAN Agreement on Transboundary Haze Pollution rules. This research is intended only for written legislation (law in books) and other legal materials. In normative research, the author will use doctrinal research methods that refer to legislation (statute approach) and a comparative approach (comparative approach). The results of this study indicate that Indonesia's accountability for cross-border smoke haze pollution due to forest fires is stipulated in Article 3 of the ASEAN Agreement on Transboundary Haze Pollution. Furthermore, the rights of countries affected by transboundary haze due to forest fires are regulated in Article 16 of the ASEAN Agreement on Transboundary Haze Pollution which states to increase preparedness and minimize risks to human health and the environment.